In defence of objective Bayesianism - Williamson, Jon. (Oxford : Oxford University Press, 2010)
Objective Bayesianism is a methodological theory that is currently applied in statistics, philosophy, artificial intelligence, physics and other sciences. This book develops the formal and philosophical foundations of the theory, at a level accessible to a graduate student with some familiarity with mathematical notation.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Bayesian statistical decision theory; Knowledge, Theory of; Reasoning -- Mathematical models